IDENTIFICATION OF ELECTROMAGNETIC FIELDS RADIATION INTENSITY ON MEDIUM VOLTAGE NETWORK EQUIPMENT - Siregar, Niko; Kurnianto, Rudi; Imansyah, Fitri; Yacoub, Redi; Kusumawardhani, Eka (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2023)
This research is about how to identify electromagnetic fields radiation intensity with measuring the electric fields and magnetic fields then compare it to the radiation exposure standards for public from ICNIRP. With the experimental method directly to the 15 randomize research sites in Pontianak city, each measurement   on 1 site done on 4 sides, front, back, right and left of the objects and each sides done measurement 5 times on different distance from 1 "“ 5 m.   The objects that has been measured are Transformer, which is very high value of electromagnetic fields compare it to any other medium voltage network equipment. The results still so much lower value than the exposure standards for public, but according to Anies reference there will be some effects about this if the public been exposed to radiation for too long, there are psychological and physicalogical effects. Hopefully this research could be referred to the public to consider the dangers exposed to radiation exposure of electromagnetic fields by medium voltage network equipment.